Secondary Teacher Education in the French-speaking community of Belgium: professional and identity related challenges - Cattonar, Branka (Swiss Journal of Educational Research, 2018)
In the French-speaking community of Belgium, the training of secondary teachers is regularly placed, for about fifteen years, in the center of political debates. At the beginning of 2000s, public authorities introduce it as a «vector of transformation of the educational system» and they decree an important reform concerning its contents and promoting the model of the «reflexive practitioner». At the beginning of 2010s, their training is presented as a «key factor of the improvement of the quality of the educational system» and its masterization is put on the political agenda. Based on data from several studies about teachers policies and the construction of their professional identity, the article discusses the professional and identity related challenges of the recent evolutions of training promoted by public authorities.